Нужно воспользоваться формулой разности квадратов практически во всех примерах: (a - b)(a + b) = a² - b².
Выполните умножение:
1) 5b(b - 1)(b + 1) = 5b(b² - 1) = 5b³ - 5b;
2) (c + 2)(c - 2) · 8c² = (c² - 4) · 8c² = 8c⁴ - 32c²;
3) (m - 10)(m² + 100)(m + 10) = (m - 10)(m + 10)(m² + 100) =
= (m² - 100)(m² + 100) = m⁴ - 10 000;
4) (a² + 1)(a² - 1)(a⁴ + 1) = (a⁴ - 1)(a⁴ + 1) = a⁸ - 1;
Упростите выражение:
1) (x + 1)(x - 1) - (x + 5)(x - 5) + (x + 1)(x - 5) = x² - 1 - (x² - 25) + x² - 5x + x - 5 = x² - 1 - x² + 25 + x² - 4x - 5 = x² - 4x + 19;
2) 81a⁸ - (3a² - b³)(9a⁴ + b⁶)(3a² + b³) = 81a⁸ - (3a² - b³)(3a² + b³)(9a⁴ + b⁶) = 81a⁸ - (9a⁴ - b⁶)(9a⁴ + b⁶) = 81a⁸ - (81a⁸ - b¹²) = 81a⁸ - 81a⁸ + b¹² = b¹².
x1 = -1
x2 = 4/3
Объяснение:
a²-b² = (a-b)(a+b)
(5x-1)²-(x-1)²=32
(5x-1-x+1)(5x-1+x-1) = 32
4x*(6x-2) = 32
24x²-8x-32 = 0 |:8
3x²-x-4 = 0
D = (-1)²-4*3*(-4) = 1+48 = 49 = 7²
x12 = (1±7)/(2*3)
x1 = -1
x2 = 4/3